What motivates West African cocoa farmers to value trees? Taking the 4 W approach to the heart of the field - Marie Ruth Dago; Irié Casimir Zo‐Bi; Isaac Kouamé Konan; Aimé Kouadio Kouassi; Stéphane Guei; Patrick Jagoret; Anny Estelle N'Guessan; Elsa Sanial; Chloé Tankam; Soulemane Traoré; Bruno Hérault (People and Nature)
Abstract West Africa, the largest cocoa‐producing region globally, has experienced significant deforestation in recent decades, leading countries to implement large‐scale agroforestry policies; however, most studies on farmers' adoption of agroforestry fail to consider the social (Who?), historical (When?), geographical (Where?), and ecological (What?) factors that influence their motivations to value trees. Drawing from a sample of 150 farmers responsible for the management of 12,096 trees, we quantified the motivations of farmers for 10 material and immaterial uses of trees and used a Bayesian modelling framework to explore the relative importance of the 4 W framework in explaining general motivations, specific to each use, as well as the varying levels of specialization in tree management strategies among farmers. The distribution of use values by category shows that the highest values are associated with (i) agronomic uses (such as shade for cocoa trees and soil fertilization), (ii) food for human consumption, (iii) social purposes, and (iv) medicinal uses. All four aspects of the 4 W framework significantly contribute to understanding farmers' deep motivations, while the influence of each 4 W determinant varies based on the specific material and immaterial uses being considered. The level of specialization or diversification in cocoa farmers' motivations is significantly influenced by their knowledge of tree species and cocoa tree density, with knowledgeable farmers exhibiting greater diversification, while higher cocoa tree density and the presence of remnant trees lead to more specialized strategies that hinder agroforestry adoption. From a political perspective, it is urgent that stakeholders involved in the promotion of agroforestry consider all dimensions of the farmer‐field system. The diversity of farmers' life histories (Who), of cultivated landscapes (Where), of field systems (What), and of time trajectories (When) present both constraints and opportunities with which farmers must contend to transition to much‐desired agroforestry systems. Read the free Plain Language Summary for this article on the Journal blog.